ANALYSIS OF SCIENCE LITERACY CAPABILITIES THROUGH DEVELOPMENT TEST OF SCIENTIFIC LITERACY SKILLS (TOSLS) INTEGRATED INTERNET OF THINGS (IOT) TECHNOLOGY - Utami, Arfiati Ulfa (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2019)
Education has an important role in preparing students to have scientific literacy skills and to be able to solve problems in daily life in the face of modern life. In science learning science literacy is very important as the development of science and technology in this era of globalization, it is necessary to develop a Test of Scientific Literacy Skills (TOSLS) as a measure to determine the extent of students' literacy abilities. The Test of Scientific Literacy Skills (TOSLS) is packaged through internet technology, where students must be able to access the internet because the Test of Scientific Literacy Skills (TOSLS) is done online. This study aims to determine the scientific literacy skills of students through the development of the Test of Scientific Literacy Skills (TOSLS) integrated Internet of Things (IoT) technology. This study uses descriptive quantitative methods. The study sample was 35 students of class VII at Srono Banyuwangi 1 Public Middle School. The research instrument used was a test in the form of a Test of Scientific Literacy Skills (TOSLS) adapted from Gormally et al. This test is given to 20 students at Srono Banyuwangi 1 Public Middle School. The average results obtained using the TOSLS test in the category are sufficient (62.52).Â Keywords: scientific literacy, Test of Scientific Literacy Skills (TOSLS), Internet of Things (IoT)